Takedown twenty - Evanovich, Janet (New York Bantam Books, 2013)
Stephanie Plum knows better than to mess with family. But when powerful mobster Salvatore "Uncle Sunny" Sunucchi goes on the lam in Trenton, it's up to Stephanie to find him. Even Trenton's cop, Joe Morelli, has skin in the game, because "just Stephanie's luck" the godfather is his actual godfather.
Includes excerpt from "The Heist" (pages 299-307).
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Trenton (N.J.) -- Fiction; Mystery and detective stories; Mystery fiction